Draft Annual Plan 1987-88 Volume : XI Hill Areas Government of Assam - Planning Commission (Planning Commission, 1987)
During the year construction of buildings for a 100 bedded District hospitals at Haflong is being completed. Construction of buildings for addition of 40 beds in Diphu Civil Hospital is being started. Construction of buildings for establishment of a 30 bedded T.B.hospital, a buildings, for Medical Store, a barrack for 20 Nurses, quarter for five married nurses and quarter for 20 Grade IV-staff at Haflong Civil Hospital will remain in progress.
Government of Assam